2019
DOI: 10.26599/jnr.2019.9040013
|View full text |Cite
|
Sign up to set email alerts
|

Hand function recovery using nerve segment insert grafting in patients with chronic incomplete lower cervical spinal cord injury: a preliminary clinical report

Abstract: Objective:The objective of this study was to show that hand functions could be recovered using nerve segment insert grafting in quadriplegic patients with chronic incomplete lower cervical spinal cord injury (CSCI) (C5/6/7/8).Methods:A retrospective analysis was performed in 18 quadriplegic patients (12 male and 6 female patients; mean age, 27 years; age range, 17–55 years) with chronic incomplete lower CSCI who had undergone nerve segment insert grafting from January 2001 to June 2015. Among the 18 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Recent clinical reports have described the role of these methods in neurological function recovery in patients with SCI [139][140][141].…”
Section: Nerve Bridgingmentioning
confidence: 99%
“…Recent clinical reports have described the role of these methods in neurological function recovery in patients with SCI [139][140][141].…”
Section: Nerve Bridgingmentioning
confidence: 99%
“…Even in late phase (> 4 years) high cervical SCI, patients still achieved beneficial outcomes from nerve transfers for motor and sensory restoration [48]. Ding et al [49] reported that long-term follow-up studies of nerve segment insert grafting showed significant hand function recovery in quadriplegic patients with chronic incomplete lower cervical SCI.…”
Section: Neurorestorative Surgerymentioning
confidence: 99%
“…Hand gripping or grasping is a basic movement that involves flexion and extension of multiple joints. Up to now, the studies on human hand grip mainly focus on the range of motion (ROM), including active, passive and functional ROMs [ 11 , 12 , 13 , 14 , 15 ], which are measured statically. Many robotic hands claimed that their ROMs can reach or be close to that of normal hands [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%